Mobilising around Europe: a conceptual framework and introduction to the special section. (4th March 2022) - van Kessel, Stijn; Fagan, Adam
ABSTRACT: This article provides a conceptual framework and introduction to the special section 'Mobilising around Europe: pro and anti-EU politics in an era of populism and nationalism'. By means of its four articles, the special section seeks to address the 'politicisation of Europe' outside of the conventional party-political arena. Whilst the future of European integration has become increasingly contested, not least due to the rise of Eurosceptic political parties of the populist radical right, we observe that politicisation has also occurred in the protest arena through grassroots activism. The contributions in this special section analyse these mobilisations, which have thus far received limited scholarly attention, and the positions and frames activists and various social movement organisations (SMOs) adopt concerning the future of European integration. By doing this, these articles reveal the often complex and context-dependent stances towards 'Europe' amongst actors across the ideological spectrum, which extend beyond dichotomous pro-/anti-EU positions.